Children's talk about fathers' regret: making sense of fathers' violence against mothers - Arnell, Linda 19XX- (Journal of family violence, 2024)
Purpose: The aim of this study is to investigate children’s sense-making about their fathers’ attitudes about using violence against the child’s mother. More specifically, we examine various ways in which the children reflect on whether, and if so how, their father showed regret. Method: This study used data from interviews with 31 children (14 boys and 17 girls) aged between 10 and 14 years, using a semi-structured interview guide. The children’s narratives were analyzed using discourse analysis. Results: We found that most of the children in this study positioned their fathers as regretful in relation to two discourses—on violence and on fatherhood—that are prominent in the interviews. Some children, however, positioned their fathers as inconsistent or non-regretful, saying they did not express regret emotionally, did not change their behavior, did not communicate regret, or communicated it in a self-contradictory way. In their narratives the children sometimes used interpretative repertoires—about feelings, actions, and communication—to explain why they thought their father did or did not regret his use of violence. Conclusion: Positioning one’s father as regretful after having committed IPV can be a way to make the father’s attitudes about the violence understandable, both to the children and to others. Discourses on violence and fatherhood can, however, constrain children’s narratives about their fathers’ violence, which is important to keep in mind when working with children who have been exposed to IPV and making decisions that concern them.